KEPAILITAN PERSEROAN TERBATAS SUDUT PANDANG TANGGUNG JAWAB DIREKSI - Yanuarsi, Susi (Faculty of Law, University of Palembang, 2020)
Each member of the Board of Directors must also be of good faith and full responsibility in carrying out his duties for the benefit of the company. If in carrying out their duties there is an indication that a director misused the power given to him for personal gain and caused financial losses that led to the bankruptcy of the company, then a director can be held personally accountable or his personal assets can be used as collateral for repayment of the company's debts that are in the company bankruptcy.